Plerixafor as preemptive strategy results in high success rates in autologous stem cell mobilization failure. Issue 4 (31st August 2016) - Worel, Nina; Fritsch, Gerhard; Agis, Hermine; Böhm, Alexandra; Engelich, Georg; Leitner, Gerda C.; Geissler, Klaus; Gleixner, Karoline; Kalhs, Peter; Buxhofer‐Ausch, Veronika; Keil, Felix; Kopetzky, Gerhard; et al.
Abstract: Plerixafor in combination with granulocyte‐colony stimulating factor (G‐CSF) is approved for autologous stem cell mobilization in poor mobilizing patients with multiple myeloma or malignant lymphoma. The purpose of this study was to evaluate efficacy and safety of plerixafor in an immediate rescue approach, administrated subsequently to G‐CSF alone or chemotherapy and G‐CSF in patients at risk for mobilization failure. Eighty‐five patients mobilized with G‐CSF alone or chemotherapy were included. Primary endpoint was the efficacy of the immediate rescue approach of plerixafor to achieve ≥2.0 × 10 6 CD34 + cells/kg for a single or ≥5 × 10 6 CD34 + cells/kg for a double transplantation and potential differences between G‐CSF and chemotherapy‐based mobilization. Secondary objectives included comparison of stem cell graft composition including CD34 + cell and lymphocyte subsets with regard to the mobilization regimen applied. No significant adverse events were recorded. A median 3.9‐fold increase in CD34 + cells following plerixafor was observed, resulting in 97% patients achieving at least ≥2 × 10 6 CD34+ cells/kg. Significantly more differentiated granulocyte and monocyte forming myeloid progenitors were collected after chemomobilization whereas more CD19 + and natural killer cells were collected after G‐CSF. Fifty‐two patients underwent transplantation showing rapid and durable engraftment, irrespectively of the stem cell mobilization regimen used. The addition of plerixafor in an immediate rescue model is efficient and safe after both, G‐CSF and chemomobilization and results in extremely high success rates. Whether the differences in graft composition have a clinical impact on engraftment kinetics, immunologic recovery, and graft durability have to be analysed in larger prospective studies.